2022
DOI: 10.3389/fpsyg.2022.771626
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Intervention to Improve Communication and Patient Safety in Obstetrics: Examination of the Health Action Process Approach

Abstract: BackgroundHuman failure and a lack of effective communication are the main reasons for preventable adverse events, compromising patient safety in obstetrics. In order to improve safety, team and communication interventions have been implemented but lack feasibility in obstetric care. Psychological models such as the health action process approach might help to improve interventions.MethodsIn a cross-sectional online survey with N = 129 healthcare workers (Study 1) and a paper-pencil survey with N = 137 obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This study demonstrated such a categorization approach which should be implemented in practice and used for research. Future trainings can make use of this categorization approach [ 12 ] but also the training used in this study [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated such a categorization approach which should be implemented in practice and used for research. Future trainings can make use of this categorization approach [ 12 ] but also the training used in this study [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, N = 4 midwives who had not been trained before took part in the microteaching sessions. A detailed overview of the training content, exercises, and goals as well as the behavior planning intervention and microteaching have been published elsewhere [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Criticism about unclear information, such as uncertainty about the progress of the birth, a lack of important information for decision making or unsettling statements, was also voiced. A recently published study emphasized the importance of communication during birth and the postpartum stage to improve women’s satisfaction [ 33 ]. In this study, the provision of clear information by the HCWs was seen as the most helpful aspect of verbal communication [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The semistructured interview guide ( Table 2 ) includes the main topics to stimulate a detailed description of the birth experience with a focus on communication, perceived support and the subjective impact of the communication training. It was flexibly adapted to the narrative flow and developed on the basis of our previous research results and project planning [ 19 , 25 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Safe communication can be described as a multilateral process that involves sharing emotions, cognitions, and actions on a verbal and nonverbal level [ 14 ]. Although previous literature has mainly focused on communication competencies among HCWs, the literature is lacking in understanding safe communication behavior from the perspective of pregnant women and their families [ 15 , 16 ]. Previous research [ 9 ] showed that more than one-third of pregnant women reported that they felt unsure to ask questions or raise concerns while giving birth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%